Biology Textbook Graphics and Their Impact on Expectations of Understanding. Issue 5 (4th July 2017) - Wiley, Jennifer; Sarmento, David; Griffin, Thomas D.; Hinze, Scott R.
ABSTRACT: Graphics presented alongside expository science texts can have a number of positive effects for instruction, including facilitating engagement, arousing interest, and improving understanding. However, because students harbor expectations about which contexts are likely to support better understanding, the mere presence of graphics also has the potential to lead to inaccurate judgments of understanding when those graphics do not actually lead to presumed levels of performance. Previous work has demonstrated that including graphics alongside text can alter the judgment process. The present work explores different categories of instructional graphics found in biology textbooks and tests how different graphic types, classified by their form and function, can affect expectations of understanding prior to actual reading. Experiment 1 found that realistic, depictive graphics predominated in a middle school text, whereas more abstract and explanatory graphics predominated in a college text. Experiment 2 demonstrated that different categories of graphics led to differences in expectations of how helpful graphics would be for understanding.